Effectiveness of complementary nursing "wet cupping" on low-density lipoprotein (LDL) in palliative patients with hypertension - Latifin, Khoirul; Purwanto, Sigit; Idriansari, Antarini (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Nowadays, there are many people with hypertension who are not aware of it. Hypertension can be caused by various factors, based on secondary hypertension or primary hypertension. High cholesterol levels are one of the causes of increased blood pressure. Low-Density Lipoprotein (LDL) is a type of cholesterol that is not good for the body if it exceeds normal limits. Objectives: This study aimed to determine the effectiveness of complementary Wet Cupping nursing on changes in Low-Density Lipoprotein cholesterol levels in people with hypertension.  Methods: The research method used was experimental research with a pre-experimental design, namely one group pretest and posttest design. Respondents were selected using purposive sampling techniques, based on the specified inclusion criteria, totaling 16 respondents. Respondents received intervention in the form of complementary wet cupping nursing three times and this was done once a week. The instruments of this research are standard operational procedures and observation sheets for Low-Density Lipoprotein (LDL) measurement results.Results: The results of this study state that there is a less significant effect on Low-Density Lipoprotein in people with hypertension after being given complementary wet cupping treatment with a significant value of 0.717 or p-value> 0.05. Although the results of statistical tests did not show significant results, there were 56.25% of respondents who experienced a decrease in Low-Density Lipoprotein. Conclusions:. Wet cupping is a treatment method that has various benefits for the body's health and does not cause bad side effects after cupping. So wet cupping can be a recommended alternative therapy option for hypertension sufferers to control Low-Density Lipoprotein levels by doing cupping regularly.